Comparative Analysis of Cyclist Energy Cost and Drag: Able-Bodied vs. Shoulder Amputee Cyclists Using Computational Fluid Dynamics - Sampaio, Tatiana (2023)
In cycling, drag is the force that opposes the cyclist's motion and is caused by the cyclist's and their equipment's interaction with the air. The surface area of the cyclist and their equipment, such as the bike, helmet, and body postures, substantially impact how much drag they encounter. This study compared the energy cost (Ec) of an able-bodied and shoulder amputee cyclist through numerical simulations using computer fluid dynamics (CFD). According to the hypothesis, an able-bodied cyclist may use more energy at a given speed than an able-bodied cyclist. For this study, a professional male cyclist who weighs 65 kg and is 1.72 m tall took part. The estimated Ec was lower for a shoulder amputee in comparison to an able-bodied cyclist. Significant statistical differences and relationships were found between the cyclists for the 11 selected speeds. Altogether, this study allows us to conclude that, for the same conditions, an able-bodied cyclist delivers less Ec in comparison to a shoulder amputee. Such knowledge contributes to understanding cycling performance and may inform training, equipment design, and energy optimisation strategies for diverse cyclist populations.